Meditating upon God's Righteousness with Chrysostom (and Luther) - Humphrey, Edith McEwan 1954- (2018)
This study investigates the exegesis of St. John Chrysostom as he reads Galatians, particularly chs. 2 and 3, supplemented by his own choice of texts in Romans. In particular, we query his use of δικαιοσύνη, and more particularly δικαιοσύνηθεοῦ, in an ageinnocent of the Reformation arguments or the contemporary Old and New Perspectives. For the sake of illustration, the ancient theologian’s readings are at times contrasted with that of Luther: Luther has an expansive view of “works of the law” but a particular meaning for δικαιοσύνηθεοῦ; the father adduces a restricted meaning to “works of the Law” but uses δικαιοσύνηmore flexibly, while putting God’s own righteousness in the forefront. The center of his exegesis is not a theological or soteriological system, but the person and actions of Jesus, whom he depicts with delightful metaphors, alongside judicial ones, for doxological purposes.
Keywords: Bible. Galatians; Theology; God; Righteousness; Greek language; Terms; Dikaiosyne; John Chrysostom, Saint, d 407; Justice; Biblical teaching; Luther, Martin, 1483-1546; Salvation; Biblical teaching